Interdiscursivity of pedagogic discourse in the ESL classroom in primary school - Rosniah Mustaffa; Idris Aman; Nor Diyana Saupi; Noorizah Mohd Noor (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2014)
The analysis of pedagogic discourses in the classroom can reveal a great deal about teachers’ interpretation and implementation of the curriculum. Studies by previous scholars have mainly described pedagogic discourses at the surface level but neglected addressing its relevance to the curriculum. As a result, discourse practices underlying pedagogic discourses are neither identified nor explained at the fundamental level. The study reported here was carried out to identify and interpret the practices of interdiscursivity in pedagogic discourse and to relate these discourse practices to the demands of curriculum implementation. Data comprising six recordings of pedagogical discourse during ESL teaching and learning sessions in four primary schools in the state of Kelantan, Malaysia was analysed using the discursive practice dimension. Results reveal five types of discourse used by teachers in the classroom, namely requirement, argumentation, notification, description, and narration. However, only one type of discourse was used by the students in the classroom that is, responding. Overall, teachers were found to dominate the pedagogic discourse in the classroom. This indicates that the demand of the current curriculum for a student-centred classroom culture does not seem to have been implemented. This study is expected to provide a new dimension in pedagogical discourse analysis, specifically for teachers.